Incorporating risk preferences of patients in the valuation of immune checkpoint inhibitors for non-small cell lung cancer - Zaim, Remziye; Redekop, W. Ken; Uyl-de Groot, Carin A. (Frontiers in Oncology, 2023)
Immunotherapy offers a distinctive mechanism of action compared to traditional treatments, arising from additional value dimensions that may not be captured in standard health technology assessments. Cancer patients may have the expectation that immunotherapy provides durable, long-term survival gains. Moreover, some patients may be willing to take a ‘risk’ to undergo immunotherapy to achieve better survival outcomes. We reviewed quantitative methods that explored patients’ risk preferences in their non-small cell lung cancer (NSCLC) treatment choices, in PubMed (MEDLINE), from January 1, 2015, until July 1, 2022. The consideration of a value dimension (‘hope’) based on patients’ risk-seeking preferences is specifically addressed for the valuation of immune checkpoint inhibitors in NSCLC. We reported that the quantitative methods that aim to measure patients’ risk preferences or ‘hope’ empirically are emerging. Value assessments should not only comprise survival improvements for the mean or median patient but also consider methods that reflect durable, long-term overall survival gains for risk-seeking patients. However, the published evidence for incorporating ‘hope’ based on patients’ stated preferences for uncertain treatment profiles is not strong, and future research could strengthen this evidence base. We encourage further research on the development and validation of quantification methods to incorporate ‘hope’ and risk preferences of patients treated with immunotherapy for NSCLC and beyond.